Pengalaman, Dampak, Dan Strategi Untuk Mengatasi Moral Distress Perawat : Systematic Review - Restika, Indah; Erika, Kadek Ayu; Saleh, Ariyanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: Moral distress is a problem that is often overlooked in the nursing profession which is a painful psychological imbalance that results from knowing ethically appropriate actions, but cannot do it. The purpose of this systematic review is to thoroughly investigate the experience of nurses' moral distress and the range of impacts that they cause and the strategies for overcoming moral distress to nurses.Method: Literature search on electronic databases from journals that have been published through ProQuest, PubMed, ScienceDirect, and Google Scholar from January 1, 2010, to September 1, 2019.Results: The intensity and frequency of moral distress experienced by nurses tend to vary. This result is due to differences in individual characteristics as well as workplace characteristics, duties, and responsibilities. The impact caused by moral distress very much includes the deterioration of the physical and mental health of nurses, provision of care, job satisfaction, and unsustainable care, poor communication, limited patient advocacy, lack of care, decreased job satisfaction, burnout and increased nursing turnover. Strategies that can be done to overcome the problem of moral distress are the application of adaptation models and individual approaches and collaborative approaches by providing ethical education to nurses and professionals in hospitals.Conclusion: Moral distress has many negative effects on both the nurse, patient and the quality of nursing care. Various strategies can be applied to overcome the problems of moral distress experienced by nurses, namely the adoption of adaptation models and individual approaches and collaborative approaches by providing ethical education to nurses and professionals in hospitals.Keywords: Moral distress, moral conflict, moral problems, nurses.